Optimization of Soil Stabilization Techniques Using Nanomaterials for Enhanced Foundation Performance - Reja Putra Jaya; Kristianus Tommy Hendryarto; Suwandi (Universitas Sains dan Teknologi Komputer, 2025)
Soil stabilization is a crucial aspect of geotechnical engineering aimed at enhancing bearing capacity and structural load resistance. Conventional methods, such as cement and lime, are commonly used but contribute to high carbon emissions, necessitating the exploration of more sustainable alternatives. One promising approach is the utilization of nanomaterials in soil stabilization. This study evaluates the effectiveness of nano-silica, nano-clay, and graphene oxide in improving soil properties and identifies the optimal dosage for practical applications. Laboratory experiments were conducted to measure Unconfined Compressive Strength (UCS), permeability, and dry density following nanomaterial treatment. The results demonstrate that graphene oxide (1.5%) yields the highest UCS increase, reaching 330 kPa, compared to 120 kPa in untreated soil. Nano-silica (2.5%) also significantly improves UCS to 315 kPa, while nano-clay (3.0%) exhibits the most effective permeability reduction to 6.2 × 10⁻⁵ cm/s. Statistical analysis using Response Surface Methodology (RSM) confirms that an optimal nanomaterial dosage can effectively enhance soil stability without compromising other physical properties. This study contributes to the advancement of nanotechnology applications in geotechnical engineering, providing an efficient and environmentally friendly alternative to conventional stabilization techniques. The findings offer a foundation for real-world implementation of nanomaterial-based soil stabilization and support the development of more sustainable infrastructure solutions.